Oral health-related quality of life and levels of anxiety and depression in individuals with oral potentially malignant disorders - Rhayane da Conceição Monteiro; Igor Ferreira Borba de Almeida; Nataly Ferreira de Jesus Pinto; Maria da Conceição Andrade; Márcio Campos Oliveira (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial)
Objectives: To evaluate oral health-related quality of life and possible correlations with anxiety and depression in patients with oral potentially malignant disorders. Methods: This cross-sectional study was carried out in a reference center for oral lesions in the interior of the state of Bahia from February 2022 to January 2023, using the questionnaires Oral Health Impact Profile-14, Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9. Results: There was a slight change in the oral health-related quality of life of individuals in the sample, with a prevalence of responses to psychological discomfort, psychological incapacity, and physical pain domains. In addition, 39.7% and 17.9% of patients were identified as likely having generalized anxiety and depressive symptoms, respectively. When relating the levels of anxiety and depression with the perception of oral health-related quality of life, a positive correlation was found (p<0.0001). Conclusions: Patients with oral potentially malignant disorders showed a slight change in oral health-related quality of life. However, there was a positive correlation between the perception of oral health-related quality of life and levels of anxiety and depression.